'Out of Sight, But Not Out of Mind': A Collaborative Reflective Case Study on Including Participants with Invisible Disabilities in LIS Research. Issue 1 (2nd January 2023) - Muir, Rebecca; Coe, Mary
ABSTRACT: The aim of this research project was to explore the inclusion of people with invisible disabilities (PwIDs) as library and information science (LIS) research participants. At least 30 percent of Australians with a disability will have an invisible disability, such as autism, mental health, brain injuries, intellectual or learning disabilities, sensory disabilities, and neurodiversity. Yet despite constituting a distinct part of the population, the voices of people with invisible disabilities are often missing in LIS research. We critically reflected on our experiences as practitioner-researchers by individually and collaboratively documenting and evaluating our approaches to research and the context in which we engaged with PwIDs as participants in our studies. We conclude that creating a research environment that welcomes the participation of PwIDs starts before the study begins and continues throughout the research process. Our recommendations for other LIS researchers is to create welcoming and inclusive research environments as an integral part of study design; this includes being aware that participants may have invisible disabilities which may, or may not, be disclosed. Based on our critical reflection and a review of the literature, we suggest ways that researchers can better create a welcoming environment for PwIDs.